184 Utilizing Breeding Indictors for an Effective AI Program in Brahman Cows. (28th November 2020) - DeShazo, Emily K; Reese, Sydney T; Franco, Gessica A; Neuendorff, Don A; Randel, Ron; Pohler, Ky
Abstract: Estrus detection is crucial to an effective AI program. The objective of this study was to assess whether Estrotect Breeding Indicators were comparable to vasectomized gomer bulls wearing chin ball markers to accurately and efficiently identify estrus. It was hypothesized that Estrotect Breeding Indicators will accurately and more efficiently detect estrus than gomer bulls. On day 0, an Estrotect Breeding Indicator was placed on Brahman cows (n = 204) that were kept with four vasectomized bulls for the following 45-day study period. Once estrus was detected via activated heat patch, cows were artificially inseminated 14 hr later and the bull score was recorded on a scale from 1–3 (1- no bull marks; 3- solid bull marks). Cows were continually monitored for return to estrus and a pregnancy diagnosis was conducted on day 110. All cows displaying estrus (n = 137) had fully activated patches, while 67 cows were anestrous for the trial duration. A ROC curve analysis indicated that the sensitivity of the bulls detecting estrus was 77.4% compared with the Estrotect Breeding Indicators. Out of the cows with a fully activated patch, 62.77% (86/137) became pregnant to AI. Of these, 17.4% (15/86) of pregnant cows received a bull score of 1 or 2, meaning there were little to no marks left from the bulls. Failure of bulls to identify estrus can be attributed to bulls' loss of energy, cows displaying homosexual behavior, bulls staying with a chosen cow, or even calves preventing the bull access to the cows in estrus. In conclusion, the patches detected estrus in a greater number of cows than the action of vasectomized bulls wearing chin ball markers leading to an increased pregnancy rate.